Loneliness Across the Life Span. (March 2015) - Qualter, Pamela; Vanhalst, Janne; Harris, Rebecca; Van Roekel, Eeske; Lodder, Gerine; Bangee, Munirah; Maes, Marlies; Verhagen, Maaike
Most people have experienced loneliness and have been able to overcome it to reconnect with other people. In the current review, we provide a life-span perspective on one component of the evolutionary theory of loneliness—a component we refer to as the reaffiliation motive (RAM). The RAM represents the motivation to reconnect with others that is triggered by perceived social isolation. Loneliness is often a transient experience because the RAM leads to reconnection, but sometimes this motivation can fail, leading to prolonged loneliness. We review evidence of how aspects of the RAM change across development and how these aspects can fail for different reasons across the life span. We conclude with a discussion of age-appropriate interventions that may help to alleviate prolonged loneliness.